Polyester film and polarizing plate comprising same

By using a polyester film with a low linear expansion coefficient and a slow axis direction adjustment and a layer of easy adhesive is provided thereon, the problems of rainbow spots and polarizer cracks caused by the polyester film in the prior art are solved, and higher durability and less rainbow spot generation are achieved.

CN119758505AInactive Publication Date: 2025-04-04NITTO DENKO CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411855210.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-01-31
Filing Date
2019-11-14
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polyester film is prone to rainbow spots in image display devices, and it is prone to cause cracks in polarizers when temperature changes, affecting its durability.

Method used

A polyester film with a linear expansion coefficient of 3.5×10-5/℃ is used, and an easy adhesive layer is provided thereon. By adjusting the slow axis direction and linear expansion coefficient of the polyester film, the occurrence of rainbow spots is reduced and the durability of the polarizer plate is improved.

Benefits of technology

It effectively reduces the occurrence of rainbow spots in the image display device, and prevents cracks of the polarizer in an environment with high temperature and large temperature changes, thereby improving the durability of the polarizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005191620300000241
    Figure BDA0005191620300000241
  • Figure HDA0005191620310000011
    Figure HDA0005191620310000011
  • Figure HDA0005191620310000012
    Figure HDA0005191620310000012
Patent Text Reader

Abstract

The invention relates to a polyester film and a polarizing plate comprising the same. Provided is a polyester film which, when applied to an image display device, exhibits little generation of rainbow spots and contributes to improvement of the durability of a polarizing plate. This polyester film has a linear expansion coefficient in a first direction of 3.5 * 10 <-5 > / DEG C or less and a linear expansion coefficient in a second direction orthogonal to the first direction of 3.5 * 10 <-5 > / DEG C or less, and has a slow axis in a direction of-5 DEG C to 5 DEG C with respect to the first direction.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application filed on November 14, 2019, with application number 201980090908.7 and invention name “Polyester film, and polarizing plate comprising the same”. Technical Field

[0002] The present invention relates to a polyester film and a polarizing plate comprising the polyester film. Background Art

[0003] In image display devices (e.g., liquid crystal display devices, organic EL display devices), due to their image forming methods, a polarizing plate is usually arranged on at least one side of the display unit. In recent years, image display devices have a tendency to further diversify their functions and uses, and are required to withstand use in more severe environments. The polarizing plate usually has a structure in which a polarizer is clamped by two protective films. As protective films, cellulose triacetate, acrylic resins, cycloolefin resins, etc. are widely used. On the other hand, from the perspective of durability as described above, it is proposed to use a polyester film such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) with excellent mechanical properties, chemical resistance, and moisture barrier properties as a polarizer protective film (e.g., Patent Document 1). However, although the polyester film has excellent mechanical properties, it has birefringence, and therefore sometimes becomes the cause of deterioration in visual recognition such as rainbow spots. In particular, with the high brightness and high color purity of image display devices in recent years, the problem of such rainbow spots is significant.

[0004] On the other hand, conventionally used polarizing plates using a protective film formed of cellulose triacetate, acrylic resin or cycloolefin resin may sometimes generate cracks in the polarizing element due to temperature changes. In recent years, as image display devices become thinner, thinner polarizing elements are required. On the other hand, image display devices that are expected to be used at high temperatures are increasing. Therefore, there is a strong demand for polarizing plates that do not generate cracks in the polarizing element and have excellent durability.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 8-271733 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The present invention has been made to solve the above-mentioned conventional problems, and a main object of the present invention is to provide a polyester film which generates less rainbow spots when used in an image display device and contributes to improving the durability of a polarizing plate.

[0010] Solutions for solving problems

[0011] The linear expansion coefficient of the polyester film of the present invention in the first direction is 3.5×10 -5 / °C or less, and the linear expansion coefficient in the second direction orthogonal to the first direction is 3.5×10 -5 / °C or less, and the polyester film has a slow axis in a direction of -5° to 5° with respect to the first direction.

[0012] In one embodiment, the polyester film has a crystallinity of 30% or more as measured by DSC.

[0013] According to another aspect of the present invention, there is provided a polarizing plate including a polarizer and the above-mentioned polyester film disposed on one side of the polarizer.

[0014] In one embodiment, the polarizer has a thickness of 20 μm or less.

[0015] In one embodiment, the polarizing plate further includes an easy-adhesion layer disposed on the polarizer side of the polyester film.

[0016] In one embodiment, the easy-adhesion layer contains fine particles.

[0017] In one embodiment, the thickness of the easy-adhesion layer is 0.35 μm or less.

[0018] In one embodiment, the refractive index of the easy-adhesion layer is 1.55 or less.

[0019] Effects of the Invention

[0020] According to the present invention, by selectively reducing the linear expansion coefficient in a predetermined direction, it is possible to provide a polyester film which generates less rainbow spots when combined with a polarizer and contributes to improving the durability of the polarizing plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention.

[0022] Figure 2 It is a schematic cross-sectional view of a polarizing plate according to another embodiment of the present invention.

[0023] Description of Reference Numerals

[0024] 10 polarizers

[0025] 20 Polyester film

[0026] 30 Adhesive layer

[0027] 40 Easy bonding layer

[0028] 100, 200 polarizing plate DETAILED DESCRIPTION

[0029] Hereinafter, preferred embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0030] A. Polyester film

[0031] The linear expansion coefficient of the polyester film of the present invention in the first direction is 3.5×10 -5 / °C or less, and the linear expansion coefficient in the second direction orthogonal to the first direction is 3.5×10 -5 / °C or less. When a polyester film having such a linear expansion coefficient is used, it can be stacked on a polarizer to effectively protect the polarizer and prevent the polarizer from cracking. In more detail, when the polyester film of the present invention is stacked on a polarizer as a polarizer protective film to form a polarizing plate, the dimensional change of the polarizer (for example, dimensional change caused by heat) can be further suppressed by the above-mentioned polyester film. As a result, when the polyester film of the present invention is used, even in harsh environments such as high temperature and large temperature changes, cracks in the polarizer can be prevented, thereby obtaining a polarizing plate with excellent durability. In one embodiment, the above-mentioned first direction corresponds to the conveying direction (MD) when the polyester film is manufactured. In addition, the above-mentioned second direction may be equivalent to TD orthogonal to MD. The linear expansion coefficient can be determined by TMA measurement according to JIS K 7197. It should be noted that the expression "substantially parallel" includes the case where the angle formed by the two directions is 0°±10°, preferably 0°±7°, and more preferably 0°±5°.

[0032] The polyester film of the present invention has a slow axis in a direction of -5° to 5° relative to the first direction. When the slow axis is in such a range, a polyester film with less rainbow spots when combined with a polarizer can be made. More specifically, as described above, when a polarizer and a polyester film are stacked to form a polarizing plate in a manner such that the absorption axis of the polarizer is approximately parallel to the first direction, rainbow spots can be effectively prevented.

[0033] The angle between the first direction and the slow axis is preferably -3° to 3°, more preferably -1° to 1°, particularly preferably -0.5° to 0.5°, and most preferably 0°. When it is within such a range, the above effect is more remarkable.

[0034] The linear expansion coefficient of the polyester film in the first direction is preferably 3.0×10 -5 / °C or less, more preferably 2.5×10 -5 / °C or less, more preferably 1.5×10 -5 / °C or less, particularly preferably 1.3×10 -5 / ℃ or less. When it is within this range, the above effect is more significant. The smaller the linear expansion coefficient of the polyester film in the first direction, the better. Its lower limit is, for example, 0.3×10 -5 / ℃(preferably 0.1×10 -5 / °C, more preferably 0×10 -5 / ℃).

[0035] The linear expansion coefficient of the polyester film in the second direction is preferably 3.4×10 -5 / °C or less, more preferably 2.3×10 -5 / ℃ or less. When it is in this range, the above effect is more significant. The smaller the linear expansion coefficient of the polyester film in the second direction, the better. Its lower limit is, for example, 1×10 -5 / ℃(preferably 0.5×10 -5 / °C, more preferably 0.3×10 -5 / ℃).

[0036] Typically, the polyester film can be a stretched film obtained through a stretching process. By appropriately adjusting the manufacturing conditions in the stretching process, the linear expansion coefficients in the first and second directions (as well as the in-plane phase difference Re (590) described later) can be well controlled. As a result, a polyester film having excellent properties for a polarizer protective film from the perspective of rainbow spots and durability as described above can be obtained. As the above-mentioned manufacturing conditions, stretching conditions (stretching temperature, stretching ratio, stretching speed, MD / TD stretching sequence), preheating temperature before stretching, heat treatment temperature after stretching, heat treatment time after stretching, relaxation rate in the MD / TD direction after stretching, etc. can be listed. The stretching temperature, stretching ratio and stretching speed can be appropriately adjusted according to each MD / TD.

[0037] The in-plane phase difference Re(590) of the polyester film is, for example, greater than 0 nm and less than 10000 nm. It should be noted that the in-plane phase difference Re(λ) is the in-plane phase difference of the film measured at 23°C with light of a wavelength of λ nm. Therefore, Re(590) is the in-plane phase difference of the film measured with light of a wavelength of 590 nm. For Re(λ), when the thickness of the film is set to d(nm), it is calculated by the formula: Re(λ) = (nx-ny) × d. Here, nx is the refractive index in the direction where the refractive index in the plane is the largest (i.e., the slow axis direction), and ny is the refractive index in the direction orthogonal to the slow axis in the plane.

[0038] The crystallinity of the polyester film measured by differential scanning calorimetry (DSC) is preferably 30% or more, more preferably 40% or more, and further preferably 50% or more. The upper limit of the crystallinity is, for example, 70%. When it is within this range, a polyester film having excellent heat resistance and mechanical properties and suitable as a polarizer protective film can be obtained.

[0039] The thickness of the polyester film is typically 10 μm to 100 μm, preferably 20 μm to 80 μm, and more preferably 20 μm to 50 μm.

[0040] The total light transmittance of the polyester film is preferably 80% or more, more preferably 85% or more, further preferably 90% or more, and particularly preferably 95% or more. The haze of the polyester film is preferably 1.0% or less, more preferably 0.7% or less, further preferably 0.5% or less, and particularly preferably 0.3% or less.

[0041] The moisture permeability of the polyester film is preferably 100 g / m 2 24 hr or less, more preferably 50 g / m 2 24 hr or less, more preferably 15 g / m 2 · 24 hr or less. When it is within such a range, a polarizing plate excellent in durability and moisture resistance can be obtained.

[0042] The polyester film of the present invention is formed of a polyester resin. The polyester resin can be obtained by condensation polymerization of a carboxylic acid component and a polyol component.

[0043] As the carboxylic acid component, aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids can be listed. As aromatic dicarboxylic acids, for example, terephthalic acid, isophthalic acid, benzylmalonic acid, 1,4-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, 4,4'-oxybenzoic acid, and 2,5-naphthalene dicarboxylic acid can be listed. As aliphatic dicarboxylic acids, for example, malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, trimethyl adipic acid, pimelic acid, 2,2-dimethyl glutaric acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, itaconic acid, thiodipropionic acid, and diglycolic acid can be listed. As alicyclic dicarboxylic acids, for example, 1,3-cyclopentane dicarboxylic acid, 1,2-cyclohexane dicarboxylic acid, 1,3-cyclopentane dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, 2,5-norbornane dicarboxylic acid, and adamantane dicarboxylic acid can be listed. The carboxylic acid component may be a derivative such as an ester, a chloride, or an anhydride, and includes, for example, dimethyl 1,4-cyclohexanedicarboxylate, dimethyl 2,6-naphthalene dicarboxylate, dimethyl isophthalate, dimethyl terephthalate, and diphenyl terephthalate. The carboxylic acid component may be used alone or in combination of two or more.

[0044] As the polyol component, representative examples include diols. As diols, aliphatic diols, alicyclic diols, and aromatic diols can be listed. As aliphatic diols, for example, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propylene glycol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2,2-dimethyl-1,3-propylene glycol (neopentyl glycol), 2-ethyl-2-butyl-1,3-propylene glycol, 2-ethyl-2-isobutyl-1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and 2,2,4-trimethyl-1,6-hexanediol can be listed. As alicyclic diols, for example, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, spirodiol, tricyclodecane dimethanol, adamantanediol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol can be listed. As aromatic diols, for example, 4,4'-thiodiphenol, 4,4'-methylenediphenol, 4,4'-(2-norbornyl)diphenol, 4,4'-dihydroxybiphenol, o-dihydroxybenzene, m-dihydroxybenzene, and p-dihydroxybenzene, 4,4'-isopropylidenephenol, 4,4'-isopropylidenebis(2,6-dichlorophenol), 2,5-naphthalene diol and p-xylene glycol can be listed. The polyol component can be used alone or in combination of two or more.

[0045] As the polyester resin, polyethylene terephthalate and / or modified polyethylene terephthalate are preferably used, and polyethylene terephthalate is more preferably used. When these resins are used, a polyester film having excellent mechanical properties and less rainbow spots can be obtained. Polyethylene terephthalate and modified polyethylene terephthalate can be used in a mixed manner.

[0046] As modified polyethylene terephthalate, for example, a modified polyethylene terephthalate containing a constituent unit derived from diethylene glycol, 1,4-butanediol, 1,3-propylene glycol or isophthalic acid can be cited. The proportion of diethylene glycol in the polyol component is preferably more than 0 mol% and less than 10 mol%, more preferably more than 0 mol% and less than 3 mol%. The proportion of 1,4-butanediol in the polyol component is preferably more than 0 mol% and less than 10 mol%, more preferably more than 0 mol% and less than 3 mol%. The proportion of 1,3-propylene glycol in the polyol component is preferably more than 0 mol% and less than 10 mol%, more preferably more than 0 mol% and less than 3 mol%. The proportion of isophthalic acid in the carboxylic acid component is preferably more than 0 mol% and less than 10 mol%, more preferably more than 0 mol% and less than 8 mol%. When it is in such a range, a polyester film with good crystallinity can be obtained. In addition, the mol % described above is the mol % relative to the total amount of all repeating units in the polymer.

[0047] The weight average molecular weight of the polyester resin is preferably 10,000 to 100,000, more preferably 20,000 to 75,000. With such a weight average molecular weight, a film that is easy to handle during molding and has excellent mechanical strength can be obtained. The weight average molecular weight can be measured by GPC (solvent: THF).

[0048] In one embodiment, a polyester film with an easy-adhesive layer is provided. The easy-adhesive layer, for example, comprises an aqueous polyurethane and an oxazoline-based crosslinking agent. The details of the easy-adhesive layer are described in, for example, Japanese Patent Publication No. 2010-55062. All the records of the publication are incorporated herein by reference.

[0049] In one embodiment, the easy-adhesive layer comprises any appropriate particles. By forming an easy-adhesive layer comprising particles, the adhesion generated during winding can be effectively suppressed. The particles can be inorganic particles or organic particles. As inorganic particles, for example, inorganic oxides such as silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, calcium phosphate, etc. can be listed. As organic particles, for example, silicone resins, fluorine resins, (meth) acrylic resins, etc. can be listed. Among these, silicon dioxide is preferred.

[0050] The particle size (number average primary particle size) of the fine particles is preferably 10 nm to 200 nm, more preferably 20 nm to 60 nm.

[0051] The thickness of the adhesive layer is preferably 2 μm or less, more preferably 1 μm or less, and further preferably 0.35 μm or less. Within such a range, a polyester film with an adhesive layer can be obtained which is unlikely to impair the optical properties of other members when used in an image display device.

[0052] In one embodiment, the refractive index of the easy-adhesion layer is preferably 1.45 to 1.60. In such a range, a polyester film with an easy-adhesion layer that is not likely to hinder the optical properties of other components when applied to an image display device can be obtained. In one embodiment, the refractive index of the easy-adhesion layer is 1.54 or more.

[0053] In one embodiment, the polyester film may include an anti-blocking layer on at least one side thereof. The anti-blocking layer may be configured as the easy-adhesion layer described above. Preferably, the anti-blocking layer contains the fine particles.

[0054] (Method for producing polyester film)

[0055] The polyester film can be obtained by the following steps: a forming step of forming a film-forming material (resin composition) containing the polyester resin into a film, and a stretching step of stretching the formed film. Preferably, the stretching step includes a preheating treatment of the film before the film is stretched, and a heat treatment after the film is stretched. In one embodiment, the polyester film is provided in a strip shape (or a shape cut from a strip).

[0056] The film forming material may contain additives in addition to the above polyester resin, and may also contain solvents. As additives, any appropriate additives may be used according to the purpose. As specific examples of additives, reactive diluents, plasticizers, surfactants, fillers, antioxidants, anti-aging agents, ultraviolet absorbers, leveling agents, thixotropic agents, antistatic agents, conductive materials, flame retardants may be listed. The number, type, combination, and addition amount of the additives may be appropriately set according to the purpose.

[0057] As a method for forming a film from a film-forming material, any appropriate forming method can be used. As a specific example, compression molding, transfer molding, injection molding, extrusion molding, blow molding, powder molding, FRP molding, cast coating (e.g., cast), calendering, hot pressing, etc. can be listed. Preferably, extrusion molding or cast coating. This is because the smoothness of the film obtained can be improved to obtain good optical uniformity.

[0058] The film can be stretched in one direction or in two directions.

[0059] In one embodiment, as a stretching method for the film, uniaxial stretching is adopted, and the film is stretched in the longitudinal direction (MD).

[0060] Biaxial stretching can be sequential biaxial stretching or simultaneous biaxial stretching. Sequential biaxial stretching or simultaneous biaxial stretching is typically performed using a tenter stretching machine. Therefore, the stretching directions of the film are typically the longitudinal direction (MD) and the width direction (TD) of the film.

[0061] In one embodiment, as a stretching method for the film, successive biaxial stretching is adopted. Preferably, the polyester film is obtained by MD stretching after TD stretching. In this way, the influence of bowing generated during TD stretching can be alleviated so that the angle between the first direction (MD) of the polyester film and the slow axis is an appropriate value.

[0062] The stretching temperature is preferably Tg+5°C to Tg+50°C, more preferably Tg+5°C to Tg+30°C, and still more preferably Tg+6°C to Tg+10°C relative to the glass transition temperature (Tg) of the film. By stretching at such a temperature, a polyester film having a well-balanced control of the direction of the slow axis and the linear expansion coefficient can be obtained. In addition, a polyester film having excellent transparency can be obtained.

[0063] The stretching ratio in MD is preferably 1 to 7 times, more preferably 2.5 to 6.5 times, and further preferably 3 to 6 times. Within such a range, a polyester film having a linear expansion coefficient controlled within a desired range and having good crystallinity and excellent durability can be obtained.

[0064] The stretching ratio in TD is preferably 1 to 7 times, more preferably 1.2 to 4 times, and further preferably 1.5 to 3.5 times. Within such a range, a polyester film having a linear expansion coefficient controlled within a desired range, good crystallinity, and excellent durability can be obtained.

[0065] The ratio of the stretch ratio in TD to the stretch ratio in MD (MD stretch ratio / TD stretch ratio) is preferably 1 to 4, more preferably 1 to 2. When it is within this range, a polyester film with particularly little rainbow spots can be obtained. In addition, when the obtained polyester film is used, cracks in the polarizer can be prevented, thereby obtaining a polarizing plate with excellent durability.

[0066] The stretching speed in MD is preferably 5% / sec to 100% / sec, more preferably 8% / sec to 80% / sec, and further preferably 8% / sec to 60% / sec. Within such a range, a polyester film having excellent optical properties, good crystallinity, and excellent durability can be obtained.

[0067] The stretching speed in TD is preferably 5% / sec to 100% / sec, more preferably 8% / sec to 80% / sec, and further preferably 8% / sec to 60% / sec. Within such a range, a polyester film having excellent optical properties, good crystallinity, and excellent durability can be obtained.

[0068] The preheat treatment temperature is preferably 80° C. to 150° C., more preferably 90° C. to 130° C. In addition, the preheat treatment time is preferably 10 seconds to 100 seconds, more preferably 15 seconds to 80 seconds. Within this range, a polyester film having excellent optical properties, good crystallinity, and excellent durability can be obtained.

[0069] The temperature of the heat treatment is preferably 100°C to 250°C, more preferably 120°C to 200°C, and further preferably 130°C to 180°C. When it is in such a range, a polyester film having excellent transparency, good crystallinity, and excellent durability can be obtained. The time of the heat treatment is preferably 2 seconds to 50 seconds, more preferably 5 seconds to 40 seconds, and further preferably 8 seconds to 30 seconds. When it is in such a range, a polyester film having excellent transparency, good crystallinity, and excellent durability can be obtained.

[0070] B.Polarizing plate

[0071] Figure 1 Schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. The polarizing plate 100 comprises: a polarizer 10, and a polyester film 20 disposed on one side of the polarizer 10. As the polyester film 20, the polyester film of the present invention described in the above-mentioned item A is used. Any other appropriate polarizer protective film may be disposed on the other side of the polarizer, or no polarizer protective film may be disposed. In one embodiment, the polarizer 10 and the polyester film 20 (or other polarizer protective film) are laminated with the aid of an adhesive layer 30.

[0072] In one embodiment, the polarizing plate can be applied to an image display device in such a manner that the side provided with the polyester film becomes the visual recognition side. In addition, when the polarizing plate is applied to a liquid crystal display device, the polarizing plate provided with the polyester film can be provided on the visual recognition side or the back side of the liquid crystal unit.

[0073] Any appropriate polarizer may be adopted as the polarizer. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.

[0074] Specific examples of polarizers composed of a single-layer resin film include polyvinyl alcohol (PVA) films, partially formalized PVA films, ethylene-vinyl acetate copolymer partially saponified films, and other hydrophilic polymer films that have been dyed and stretched using dichroic substances such as iodine and dichroic dyes; polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films, etc. From the perspective of excellent optical properties, it is preferred to use a polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it.

[0075] The above-mentioned iodine-based dyeing is carried out, for example, by immersing the PVA film in an iodine aqueous solution. The stretching ratio of the above-mentioned uniaxial stretching is preferably 3 to 7 times. The stretching can be carried out after the dyeing treatment, or it can be carried out while dyeing. In addition, it is also possible to dye after stretching. As needed, the PVA film is subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. For example, by immersing the PVA film in water and washing it with water before dyeing, not only can the stains and anti-blocking agent on the surface of the PVA film be cleaned, but also the PVA film can be swollen to prevent uneven dyeing.

[0076] As a specific example of a polarizer obtained using a laminate, a polarizer obtained using the following laminate can be listed: a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate. The polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate can be made, for example, as follows: a PVA-based resin solution is applied to a resin substrate and dried to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In the present embodiment, stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, stretching may also include stretching the laminate in the air at a high temperature (for example, above 95°C) before stretching in an aqueous boric acid solution as required. The obtained laminate of resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective layer of polarizer), or the resin substrate can be peeled off from the laminate of resin substrate / polarizer, and any appropriate protective layer that meets the purpose can be stacked on the peeled surface for use. The details of the manufacturing method of such a polarizer are described in, for example, Japanese Patent Publication No. 2012-73580. All the records of the publication are cited in this specification as a reference.

[0077] The thickness of the polarizer is, for example, 1 μm to 80 μm. In one embodiment, the thickness of the polarizer is preferably 20 μm or less, and more preferably 3 μm to 15 μm. When the polyester film of the present invention is used, cracks in the polarizer can be effectively prevented, so a thin polarizer can be used even in harsh environments such as high temperature and large temperature changes.

[0078] The polarizer and the polarizer protective film (polyester film) may be laminated via any appropriate adhesive layer. Preferably, the adhesive layer is formed of an adhesive composition containing a polyvinyl alcohol-based resin.

[0079] The absorption axis direction of the polarizer is preferably approximately parallel to the first direction (representatively MD) or the second direction (representatively TD) of the polyester film, and more preferably approximately parallel to the first direction (representatively MD). When configured in this way, the polyester film and the polarizer can preferably change shape synchronously. As a result, cracks in the polarizer can be prevented.

[0080] The more consistent the angle between the slow axis angle of the polyester film and the absorption axis direction of the polarizer, the more preferred, and the angle between the two axes is preferably 0°±10°, more preferably 0°±7°, and further preferably 0°±5°. When it is in such a range, a polyester film with less rainbow spots can be obtained when applied to an image display device. It should be noted that the slow axis angle is the angle when the roller flow direction is set to 0°.

[0081] In the polarizing plate, the absolute value of the difference between the linear expansion coefficient of the polyester film in the first direction and the linear expansion coefficient of the polarizer in the direction parallel to the first direction is preferably 2.0×10 -5 / °C or less, more preferably 1.5×10 -5 / °C or less, more preferably 1.0×10 -5 / ℃ or less. When it is within this range, cracks in the polarizer can be prevented even in harsh environments such as high temperature and large temperature changes. The lower limit of the absolute value of the difference between the linear expansion coefficient of the polyester film in the first direction and the linear expansion coefficient of the polarizer in the direction parallel to the first direction is preferably as small as possible, for example, 0.1×10 -5 / ℃.

[0082] In the polarizing plate, the absolute value of the difference between the linear expansion coefficient of the polyester film in the second direction (a direction perpendicular to the first direction) and the linear expansion coefficient of the polarizer in the direction parallel to the second direction is preferably 2.0×10 -5 / °C or less, more preferably 1.5×10 -5 / °C or less, more preferably 1.0×10 -5 / ℃ or less. When it is within this range, cracks in the polarizer can be prevented even in harsh environments such as high temperature and large temperature changes. The lower limit of the absolute value of the difference between the linear expansion coefficient of the polyester film in the second direction and the linear expansion coefficient of the polarizer in the direction parallel to the second direction is preferably as small as possible, for example, 0.1×10 -5 / ℃.

[0083] In one embodiment, the absolute value of the difference between the linear expansion coefficient of the polyester film in the first direction and the linear expansion coefficient of the polarizer in the direction parallel to the first direction, and the absolute value of the difference between the linear expansion coefficient of the polyester film in the second direction (a direction orthogonal to the first direction) and the linear expansion coefficient of the polarizer in the direction parallel to the second direction are both 2.0×10-5 / ℃ or less (preferably 1.0×10 -5 When the temperature is within this range, cracks in the polarizer can be prevented even in a severe environment such as a high temperature or a large temperature change.

[0084] Figure 2 Schematic cross-sectional view of a polarizing plate according to another embodiment of the present invention. The polarizing plate 200 further includes an easy-adhesion layer 40 disposed on the polarizer 10 side of the polyester film 20. In one embodiment, the polyester film A with an easy-adhesion layer is disposed on the polarizer 10 in such a manner that the easy-adhesion layer 40 becomes the polarizer 10 side. As the easy-adhesion layer, the easy-adhesion layer described in the above-mentioned item A can be used.

[0085] C. Image display device

[0086] The polarizing plate can be applied to an image display device. Representative examples of image display devices include liquid crystal display devices and organic electroluminescent (EL) display devices. The image display device has a structure known in the industry, so a detailed description thereof is omitted.

[0087] Example

[0088] The present invention is described in detail below by way of examples, but the present invention is not limited to these examples. The measuring methods of the various properties in the examples are as follows. It should be noted that, unless otherwise specified, the "parts" and "%" in the examples are by weight.

[0089] (1) Orientation angle (direction of slow axis)

[0090] The central part of the polyester film obtained in the examples and comparative examples was cut into a square shape with a width of 50 mm and a length of 50 mm in a manner parallel to the width direction of the film to prepare a sample. The sample was measured using a Mueller matrix polarimeter (Axometrics product name "Axoscan") to measure the orientation angle θ at a wavelength of 550 nm and 23°C. It should be noted that the orientation angle θ was measured when the sample was placed parallel to the measuring table.

[0091] (2) Linear expansion coefficient

[0092] For the linear expansion coefficient of the polyester film and the polarizer, based on JIS K 7197, a thermomechanical analyzer "TMA7000" manufactured by Hitachi High-TechScience Corporation was used to increase the temperature from 30°C to 150°C at a rate of 10°C / min, and the deformation of the test film at each temperature was measured. Then, the linear expansion coefficient of the film was calculated based on the deformation in the temperature range of 30°C to 70°C. It should be noted that the case where the film size increases (expands) as the temperature rises is recorded as positive (+), and the case where the film size decreases (contracts) as the temperature rises is recorded as negative (-).

[0093] The linear expansion coefficients of the polyester film in MD (first direction) and TD (second direction) were measured. The linear expansion coefficients of the polarizer in the polarizing plate in the direction parallel to the MD and the direction parallel to the TD were measured.

[0094] (3) Crystallinity

[0095] The crystallinity of the polyester film used in the examples and comparative examples was measured by differential scanning calorimetry (DSC). The calorific value and the heat of fusion observed when the sample was heated to 300°C at 10°C / min were obtained, and the crystallinity was obtained by the following formula. It should be noted that the calorific value and the heat of fusion were measured using Q-2000 manufactured by TA Instruments.

[0096] Crystallinity (%) = (heat of fusion obtained in the measurement - calorific value obtained in the measurement) / fusion heat of polyethylene terephthalate with 100% crystallinity (119 mJ / mg) × 100

[0097] (4) Rainbow spots

[0098] A liquid crystal unit was taken out from a liquid crystal TV "45UH7500" manufactured by LGD, and the polarizing plate on the backlight side was peeled off. The polarizing plates obtained in the examples and comparative examples were attached to the surface of the liquid crystal TV from which the polarizing plates were peeled off, with the aid of an adhesive, so that the absorption axis of the polarizer was on the short side of the liquid crystal TV. The liquid crystal unit with the polarizing plates obtained in the examples and comparative examples attached was set again, and the TV was lit up to display white.

[0099] The lit liquid crystal TV was visually checked from all directions at a polar angle of 60° to observe the presence or absence of rainbow spots. Evaluation was performed based on the following criteria.

[0100] ○: No rainbow spots were observed

[0101] △: Rainbow spots are slightly observed

[0102] ×: Rainbow spots are clearly observed

[0103] (5) Dimensional changes

[0104] The polyester film used in the examples and comparative examples was cut into 100 mm × 100 mm. After that, it was placed in a heating oven at 100°C for 24 hours, and then the film was taken out and the dimensions were accurately measured again. The dimensions were confirmed with a metal ruler to find the dimensional changes. In addition, the state of the sample was visually confirmed and evaluated according to the following criteria.

[0105] ○: No significant shrinkage of 1 mm or more

[0106] ×: Shrinkage of more than 1 mm or deformation

[0107] (6) Crack test (accelerated thermal shock test)

[0108] The polarizing plates obtained in Examples and Comparative Examples were evaluated using a thermal shock tester (manufactured by ESPEC).

[0109] The polarizing plates obtained in the examples and comparative examples were cut into 50 mm in width and 150 mm in length. At this time, samples were prepared in which the absorption axis direction of the polarizer was parallel to the transverse direction (short side) of the cut polarizing plate and the transmission axis direction of the polarizer was parallel to the transverse direction (short side) of the cut polarizing plate. The surface of the polarizing plate without the laminated protective film (polyester film) was bonded to a 0.5 mm thick alkali-free glass with the aid of an acrylic adhesive to prepare the sample.

[0110] The obtained sample was placed in the test area of ​​the thermal shock tester, and the temperature in the test area was lowered from room temperature to -40°C in 30 minutes. Then, the temperature in the test area was raised to 85°C in 30 minutes, and then lowered to -40°C again in 30 minutes. The process of raising the temperature from -40°C to 85°C and lowering the temperature to -40°C was regarded as one cycle, and after repeating 100 cycles and 200 cycles, the laminate was taken out, and the presence or absence of cracks was visually confirmed, and evaluated according to the following criteria.

[0111] ◎: No cracks were observed even after 300 cycles were repeated.

[0112] ○: No cracks were observed after 200 cycles, but cracks occurred after 300 cycles.

[0113] △: No cracks were observed after 100 cycles, but cracks occurred after 200 cycles.

[0114] ×: Cracks occurred after 100 cycles were repeated.

[0115] [Manufacturing Example 1] Preparation of Polarizer A

[0116] As a substrate, a long strip of amorphous isophthalic acid copolymer polyethylene terephthalate (IPA copolymer PET) film (thickness: 100 μm) with a water absorption rate of 0.75% and a Tg of 75°C was used. One side of the substrate was subjected to corona treatment, and an aqueous solution containing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (polymerization degree 1200, acetoacetyl modification degree 4.6%, saponification degree 99.0 mol% or more, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z200") in a ratio of 9:1 was applied to the corona-treated surface and dried to form a PVA-based resin layer with a thickness of 11 μm to produce a laminate.

[0117] The obtained laminate was subjected to free-end uniaxial stretching to 2.0 times in the longitudinal direction (longitudinal direction) between rolls having different peripheral speeds in an oven at 120° C. (in-air auxiliary stretching).

[0118] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 30° C. for 30 seconds (insolubilization treatment).

[0119] Next, the polarizing plate was immersed in a dyeing bath at a temperature of 30° C. while adjusting the iodine concentration and immersion time so that the polarizing plate had a predetermined transmittance. In this example, the polarizing plate was immersed in an iodine aqueous solution containing 0.2 parts by weight of iodine and 1.5 parts by weight of potassium iodide per 100 parts by weight of water for 60 seconds (dyeing treatment).

[0120] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 3 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 30° C. for 30 seconds (crosslinking treatment).

[0121] Thereafter, the laminate was immersed in an aqueous boric acid solution (an aqueous solution obtained by mixing 4 parts by weight of boric acid and 5 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 70°C, and was uniaxially stretched (underwater stretching) in the longitudinal direction (length direction) between rollers with different peripheral speeds so that the total stretching ratio became 5.5 times.

[0122] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 30° C. (cleaning treatment), thereby obtaining a polarizer A with a removable substrate.

[0123] [Manufacturing Example 2] Preparation of Polarizer B

[0124] A polarizer B with a removable substrate was obtained in the same manner as in Production Example 1 except that the stretching ratio in the underwater stretching was 4.6 times.

[0125] [Manufacturing Example 3] Manufacture of polyester film A

[0126] A polyester resin (polyethylene terephthalate, manufactured by Bell Polyester Products, Inc., isophthalic acid modification amount: 2.5 mol% (number of moles relative to the total amount of all repeating units of the polymer), diethylene glycol modification amount: 1.0 mol% (number of moles relative to the total amount of all repeating units of the polymer), IV value: 0.77 dl / g (phenol: 1,1,2,2,-tetrachloroethane = 6:4 mixed solvent solution concentration: 0.4 g / dl) was vacuum dried at 100°C for 10 hours, and then a non-crystalline polyester resin film with a thickness of 200 μm was produced using a film forming apparatus equipped with a single screw extruder (manufactured by Toyo Seiki Co., Ltd., screw diameter: 25 mm, barrel setting temperature: 280°C), a T-die (width: 500 mm, setting temperature: 280°C), a cooling roll (setting temperature: 50°C) and a winder.

[0127] The obtained amorphous polyester resin film was subjected to simultaneous biaxial stretching using a stretching machine KAROIV manufactured by Brückner to obtain a polyester film A (slow axis angle relative to the longitudinal direction: -0.5°, in-plane phase Re (590): 80 nm, thickness: 17 μm). The stretching ratio was set to 4 times in the longitudinal direction (MD) and 3 times in the width direction (TD). The stretching temperature was set to 90°C, and the stretching speed was set to 30% / sec in both MD and TD. In addition, after the stretching treatment, a heat treatment was performed at 180°C for 10 seconds while maintaining the size.

[0128] [Manufacturing Example 4] Manufacture of polyester film I

[0129] A polyester resin (polyethylene terephthalate, manufactured by Bell Polyester Products, Inc., IV value 0.75 dl / g (phenol: 1,1,2,2,-tetrachloroethane = 6:4 mixed solvent solution concentration 0.4 g / dl) was vacuum dried at 100°C for 10 hours, and then a 200 μm thick amorphous polyester resin film was produced using a film forming apparatus equipped with a single screw extruder (manufactured by Toyo Seiki Co., Ltd., screw diameter 25 mm, barrel setting temperature: 280°C), a T die (width 500 mm, setting temperature: 280°C), a cooling roll (setting temperature: 50°C) and a winder.

[0130] The obtained amorphous polyester resin film was subjected to simultaneous biaxial stretching using a stretching machine KAROIV manufactured by Brückner to obtain a polyester film I (slow axis angle relative to the longitudinal direction: -2.5°, in-plane phase Re (590): 271 nm, thickness: 22 μm). The stretching ratio was set to 3 times in the longitudinal direction (MD) and 3 times in the width direction (TD). The stretching temperature was set to 90°C, and the stretching speed was set to 2% / sec in both MD and TD. In addition, after the stretching treatment, a heat treatment was performed at 140°C for 10 seconds while maintaining the size.

[0131] [Manufacturing Example 5] Manufacture of polyester film II

[0132] The stretching ratio was set to 2 times in the longitudinal direction (MD) and 2 times in the width direction (TD), the stretching speed was set to 2% / sec in both MD and TD, and the stretching treatment was performed at 140°C for 10 seconds. Except for this, the same operation was carried out as in Production Example 4 to obtain a polyester film II (slow axis angle relative to the longitudinal direction: -11.9°, in-plane phase Re(590): 54nm, thickness: 50μm).

[0133] [Manufacturing Example 6] Manufacture of polyester film III

[0134] The stretching ratio was set to 6 times in the length direction (MD) and 1 times in the width direction (TD) in fixed-end stretching, the stretching speed was set to 2% / sec in both MD and TD, and a heat treatment was performed at 140°C for 10 seconds after the stretching treatment. Except for this, the same operation was carried out as in Manufacturing Example 4 to obtain a polyester film III (slow axis angle relative to the length direction: -0.6°, in-plane phase Re(590): 2823nm, thickness: 41μm).

[0135] [Manufacturing Example 7] Manufacture of polyester film IV

[0136] A polyester resin (polyethylene terephthalate, manufactured by Bell Polyester Products, Inc., isophthalic acid modification amount: 2.5 mol% (number of moles relative to the total number of repeating units of the polymer), diethylene glycol modification amount: 1.0 mol% (number of moles relative to the total number of repeating units of the polymer), IV value: 0.77 dl / g (phenol: 1,1,2,2,-tetrachloroethane = 6:4 mixed solvent solution concentration: 0.4 g / dl) was vacuum dried at 100°C for 10 hours, and then a non-crystalline polyester resin film with a thickness of 100 μm was produced using a film forming apparatus equipped with a single screw extruder (manufactured by Toyo Seiki Co., Ltd., screw diameter: 25 mm, barrel setting temperature: 280°C), a T-die (width: 500 mm, setting temperature: 280°C), a cooling roll (setting temperature: 50°C) and a winder.

[0137] The obtained amorphous polyester resin film was subjected to simultaneous biaxial stretching using a stretching machine KAROIV manufactured by Brückner to obtain a polyester film IV (slow axis angle relative to the longitudinal direction: -0.9°, in-plane phase Re (590): 3191nm, thickness: 38μm). The stretching ratio was set to 7 times in the longitudinal direction (MD) and 1 times in the width direction (TD) in fixed-end stretching. The stretching temperature was set to 90°C, and the stretching speed was set to 10% / sec in both MD and TD. In addition, after the stretching treatment, a heat treatment was performed at 140°C for 10 seconds while maintaining the size.

[0138] [Manufacturing Example 8] Manufacture of polyester film V

[0139] A polyester film V (slow axis angle with respect to the longitudinal direction: 3.0°, in-plane phase Re (590): 17 nm, thickness: 50 μm) was obtained in the same manner as in Production Example 7 except that the film thickness was 50 μm and stretching was not performed.

[0140] [Manufacturing Example 9] Manufacture of polyester film VI

[0141] A polyester resin (polyethylene terephthalate, manufactured by Bell Polyester Products, Inc., isophthalic acid modification amount 2.5 mol% (number of moles relative to the total amount of all repeating units in the polymer), IV value 0.77 dl / g (phenol: 1,1,2,2,-tetrachloroethane = 6:4 mixed solvent solution concentration 0.4 g / dl) was vacuum dried at 100°C for 10 hours, and then a 170 μm thick amorphous polyester resin film was produced using a film forming apparatus equipped with a single screw extruder (manufactured by Toyo Seiki Co., Ltd., screw diameter 25 mm, barrel setting temperature: 280°C), a T die (width 500 mm, setting temperature: 280°C), a cooling roll (setting temperature: 50°C) and a winder.

[0142] The film was free-end uniaxially stretched to 2.0 times in the longitudinal direction (length direction) between rolls having different peripheral speeds in an oven at 120°C.

[0143] Next, after being immersed in water at a liquid temperature of 30°C for 120 seconds, the film was uniaxially stretched (underwater stretching) in the longitudinal direction (longitudinal direction) between rolls having different peripheral speeds while being immersed in water at a liquid temperature of 73°C so that the total stretching ratio became 5.5 times.

[0144] The obtained stretched film was heat treated at 90°C for 10 seconds using a stretching machine KAROIV manufactured by Brückner to obtain a polyester film VI (slow axis angle with respect to the longitudinal direction: -0.2°, in-plane phase Re(590): 3243 nm, thickness: 35 μm).

[0145] [Manufacturing Example 10] Manufacture of polyester film VII

[0146] A stretched film was obtained in the same manner as in Production Example 9.

[0147] The obtained stretched film was heat treated at 90°C for 10 seconds and further at 140°C for 10 seconds using a stretching machine KAROIV manufactured by Brückner to obtain a polyester film VII (slow axis angle relative to the longitudinal direction: -0.4°, in-plane phase Re(590): 4052 nm, thickness: 35 μm).

[0148] [Example 1]

[0149] The polyester film A produced in Manufacturing Example 3 was subjected to corona treatment, and an aqueous solution containing 15.2 wt % of "SUPERFLEX 210R" manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd. and 2.7 wt % of "WS-700" manufactured by Nippon Shokubai Co., Ltd. was applied thereon so that the film thickness after drying became 300 μm, and the film was dried at 80° C. for 1 minute to obtain a polyester film A with an easy-adhesive layer.

[0150] The surface of the polarizer with a substrate obtained in Manufacturing Example 1 is coated with an aqueous solution of a PVA-based resin (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER (registered trademark) Z-200", resin concentration: 3 wt%) and the above-mentioned polyester film with an easy-adhesive layer is attached. The obtained laminate is heated in an oven maintained at 60°C for 5 minutes. Thereafter, the substrate is peeled off from the PVA-based resin layer to obtain a polarizing plate (polarizer (transmittance 42.3%, thickness 5 μm) / protective film (polyester film)). It should be noted that the polyester film A and the polarizer are laminated in a manner that the MD direction of the polyester film A is approximately parallel to the absorption axis direction of the polarizer.

[0151] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0152] [Example 2]

[0153] A polarizing plate was obtained in the same manner as in Example 1 except that the polarizer obtained in Production Example 2 was used instead of the polarizer with a substrate obtained in Production Example 1. The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0154] [Comparative Example 1]

[0155] A polarizing plate was obtained in the same manner as in Example 1, except that the polyester film I produced in Production Example 4 was used instead of the polyester film A produced in Production Example 3.

[0156] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0157] [Comparative Example 2]

[0158] A polarizing plate was obtained in the same manner as in Example 1, except that the polyester film II produced in Production Example 5 was used instead of the polyester film A produced in Production Example 3.

[0159] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0160] [Comparative Example 3]

[0161] A polarizing plate was obtained in the same manner as in Example 1, except that the polyester film III produced in Production Example 6 was used instead of the polyester film A produced in Production Example 3.

[0162] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0163] [Comparative Example 4]

[0164] A polarizing plate was obtained in the same manner as in Example 1, except that the polyester film IV produced in Production Example 7 was used instead of the polyester film A produced in Production Example 3.

[0165] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0166] [Comparative Example 5]

[0167] A polarizing plate was obtained in the same manner as in Example 1 except that polyester film a (manufactured by Toyobo Co., Ltd., trade name “Cosmoshine A4100”, slow axis angle with respect to the longitudinal direction: 90°, in-plane phase Re (590): 7800 nm, thickness: 75 μm) was used instead of polyester film A produced in Production Example 3.

[0168] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0169] [Comparative Example 6]

[0170] A polarizing plate was obtained in the same manner as in Example 1 except that polyester film b (manufactured by Mitsubishi Chemical Corporation, trade name “T100-J25”, slow axis angle with respect to the longitudinal direction: 27°, in-plane phase Re(590): 525 nm, thickness: 25 μm) was used instead of polyester film A produced in Production Example 3.

[0171] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0172] [Comparative Example 7]

[0173] A polarizing plate was obtained in the same manner as in Example 1, except that the polyester film V produced in Production Example 8 was used instead of the polyester film A produced in Production Example 3.

[0174] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0175] [Comparative Example 8]

[0176] A polarizing plate was obtained in the same manner as in Example 1 except that the polyester film VI produced in Production Example 9 was used instead of the polyester film A produced in Production Example 3.

[0177] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0178] [Comparative Example 9]

[0179] A polarizing plate was obtained in the same manner as in Example 1, except that the polyester film VII produced in Production Example 10 was used instead of the polyester film A produced in Production Example 3.

[0180] The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0181] [Comparative Example 10]

[0182] A polarizing plate was obtained in the same manner as in Comparative Example 1 except that the polarizer obtained in Production Example 2 was used instead of the polarizer with a substrate obtained in Production Example 1. The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0183] [Comparative Example 11]

[0184] A polarizing plate was obtained in the same manner as in Comparative Example 3 except that the polarizer obtained in Production Example 2 was used instead of the polarizer with a substrate obtained in Production Example 1. The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0185] [Comparative Example 12]

[0186] A polarizing plate was obtained in the same manner as in Comparative Example 8 except that the polarizer obtained in Production Example 2 was used instead of the polarizer with a substrate obtained in Production Example 1. The obtained polarizing plate was subjected to the above-mentioned evaluations (1) to (6). The results are shown in Table 1.

[0187] [Table 1]

[0188]

Claims

1. A polarizing plate comprising: a polarizer, and a polyester film disposed on one side of the polarizer, The linear expansion coefficient of the polyester film in the first direction is 1.1×10 -5 / ℃~3.5×10 -5 / ℃, The linear expansion coefficient of the polyester film in the second direction orthogonal to the first direction is 1×10 -5 / ℃~3.5×10 -5 / ℃, The polyester film has a slow axis in a direction of -5° to 5° relative to the first direction. The absorption axis of the polarizer is substantially parallel to the first direction of the polyester film. The absolute value of the difference between the linear expansion coefficient of the polyester film in the first direction and the linear expansion coefficient of the polarizer in a direction parallel to the first direction is 2.0×10 -5 / ℃ below, The difference between the linear expansion coefficient of the polyester film in the second direction and the linear expansion coefficient of the polarizer in a direction parallel to the second direction (linear expansion coefficient of the polyester film in the second direction - linear expansion coefficient of the polarizer in a direction parallel to the second direction) is -2.2×10 -5 / ℃~2.0×10 -5 / ℃.

2. The polarizing plate according to claim 1, wherein The polyester film has a crystallinity of 30% or more as measured by DSC.

3. The polarizing plate according to claim 1 or 2, wherein: The polyester film is a biaxially stretched film.

4. The polarizing plate according to any one of claims 1 to 3, wherein The polarizer has a thickness of less than 20 μm. 5 . The polarizing plate according to claim 1 , further comprising an easy-adhesion layer disposed on the polarizer side of the polyester film.

6. The polarizing plate according to claim 5, wherein: The easy-adhesion layer contains fine particles.

7. The polarizing plate according to claim 5 or 6, wherein: The thickness of the easy-adhesion layer is 0.35 μm or less.

8. The polarizing plate according to any one of claims 5 to 7, wherein The refractive index of the easy-adhesion layer is 1.55 or less.

Citation Information

Patent Citations

  • Front side protective sheet for front side polarizing plate, its production and sticking method of front side protective sheet to polarizing base film

    JP1996271733A

  • Polarizer-protecting film, and polarizing plate and image display device using polarizer-protecting film

    JP2010055062A

  • Manufacturing method of thin polarizing film

    JP2012073580A

  • Optical polyester film with high surface tension and hardness

    CN106674509A

  • Polarizing plate protective film, production method for same, and polarizing plate

    CN108474892A